Capabilities of Data Quality Assurance Section and Performance of Unit in the Directorate General of Taxes: The Moderating Role of Data Quality - Utami, Nugraheni Dwi; Arifin, Imam; Tatariyanto, Firman (Scientax: Jurnal Kajian Ilmiah Perpajakan Indonesia, 2025)
Identifying data quality drivers is increasingly crucial for DGT because it helps achieve goals, maintain taxpayer compliance, increase efficiency, and improve business process accuracy. This study aims to identify whether strategic resources within an organisation influence its ability to achieve sustainable performance. Using the resource-based view theory, this study tests a moderated mediation model to examine the role of data quality on the relationship between the capabilities of the PKD Section at the tax office and the performance of that office at various locations in Indonesia. The proposed research model was validated using online surveys and structural equation modeling. The results indicate that the capabilities of the PKD Section significantly contribute to performance improvement through a path other than data. However, there is still a need to improve data quality within an organisation. Most notably, the findings demonstrate that the PKD Section's capabilities correlate with improving data quality management; however, users have not utilized the data produced by the PKD Section, nor have they supported analysis to enhance performance. Our findings confirmed that achieving data quality requires more than a technical standpoint. Instead, it must be viewed within a broader organisational framework encompassing management, resources, and culture. This research expanded the theoretical scope of capabilities and performance by introducing the concept of data quality management, which includes aspects such as planning, monitoring, assurance, and improvement. Additionally, we incorporated data quality aspects, such as data accuracy, timeliness, completeness, consistency, uniqueness, and validity, that meet the requirements of data users.